Effects of successive air and Trimix dives on human cardiovascular function - Marinovic, J.; Ljubkovic, M.; Obad, A.; Bakovic, D.; Breskovic, T.; Dujic, Z. (Medicine & Science in Sports & Exercise, 2009)
Introduction: The use of trimix (a mixture of oxygen, helium, and nitrogen) has significantly increased among the diver population. However, data indicating how trimix dives at most common depths affect the cardiovascular function are sparse. The purpose of this study was to investigate the cardiovascular effects of trimix dives and compare them with air dives and to determine whether the repetition of dives in successive days affects their extent.